2019
DOI: 10.1021/acssuschemeng.9b01239
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Reprocessable Polyhydroxyurethane Networks: Full Recovery of Crosslink Density with Three Concurrent Dynamic Chemistries

Abstract: Despite significant past efforts to exploit green, renewable precursors in polymeric materials and to improve the recyclability and reprocessability of nonisocyanate polyurethane (NIPU) networks, no single study has previously investigated biobased polyhydroxyurethane (PHU) network reprocessability. Renewable, dynamic PHU networks were synthesized by reacting bioderived polyfunctional cyclic carbonates, carbonated soybean oil (CSBO), and sorbitol ether carbonate (SEC), with either a synthetic diamine or a biob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 47 publications
5
157
0
Order By: Relevance
“…In some of these cases, despite the disappearance of epoxide and the appearance of IR-bands for the carbonate CvO stretching were observed, the actual chemoselectivity for the CC was not reported. 255,256 Mazo and Rios observed that the addition of water (about 33 mol%) significantly accelerates the carbonation of ESBO thus obtaining the corresponding CVO under atmospheric pressure with good conversion and selectivity in 70 h (entry 18). 257 This result is in line with the known ability of water to serve as a HBD in the cycloaddition of CO 2 to epoxides.…”
Section: Catalytic Performances In the Cycloaddition Of Co 2 To Various Iefas And Evos: The Role Of Quaternary Saltsmentioning
confidence: 99%
“…In some of these cases, despite the disappearance of epoxide and the appearance of IR-bands for the carbonate CvO stretching were observed, the actual chemoselectivity for the CC was not reported. 255,256 Mazo and Rios observed that the addition of water (about 33 mol%) significantly accelerates the carbonation of ESBO thus obtaining the corresponding CVO under atmospheric pressure with good conversion and selectivity in 70 h (entry 18). 257 This result is in line with the known ability of water to serve as a HBD in the cycloaddition of CO 2 to epoxides.…”
Section: Catalytic Performances In the Cycloaddition Of Co 2 To Various Iefas And Evos: The Role Of Quaternary Saltsmentioning
confidence: 99%
“…To date, most plant‐oil‐based PUs have exhibited poor thermal and mechanical properties and also required high temperature and long periods of time for self‐repair and reprocessing. In addition, PUs incorporating active dynamic bonds usually require a costly catalyst or high energy input to activate the exchange process, which may lead to catalyst instability and thermal degradation of the matrix [8a, 10] …”
Section: Introductionmentioning
confidence: 99%
“…In the past years, there has been ample literature to report the synthesis and correlation of structure with properties of PHUs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. For instance, Endo et al [ 31 , 32 , 33 , 34 ] have reported the synthetic approaches of five- and six-membered cyclic carbonates, which can be used as the monomers of PHUs.…”
Section: Introductionmentioning
confidence: 99%